2009
DOI: 10.5194/acp-9-6273-2009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the effect of water on the heterogeneous reactions of carbonyl sulfide on the surface of α-Al<sub>2</sub>O<sub>3</sub> and MgO

Abstract: Abstract.Here we compared the heterogeneous reactions of carbonyl sulfide (OCS) on the surface of α-Al 2 O 3 and MgO and the effect of water on the reactions at 300 K using Knudsen cell -mass spectrometry, diffuse reflectance infrared Fourier transform spectroscopy, and temperature programmed reactions. H 2 S and CO 2 were found to be hydrolysis products of OCS on both α-Al 2 O 3 and MgO at ambient temperature. At low water vapor pressure (<6.8×10 −6 Torr), when water vapor pressure in the Knudsen cell reactor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 50 publications
1
36
1
Order By: Relevance
“…The decline of the initial g with RH can be ascribed to competitive adsorption between H 2 O and NO 2 , similar to the competitive adsorption of O 3 , NO 2 or COS with H 2 O on mineral oxides. 22,24,25 It has been found that a monolayer of H 2 O on kaolin is achieved at 13% RH, 6 and at 10% RH on hematite. 24 The initial g of H 2 O on mineral dust (4.2 AE 0.7 Â 10 À2 ) 42 is much larger than that of NO 2 , as discussed above.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The decline of the initial g with RH can be ascribed to competitive adsorption between H 2 O and NO 2 , similar to the competitive adsorption of O 3 , NO 2 or COS with H 2 O on mineral oxides. 22,24,25 It has been found that a monolayer of H 2 O on kaolin is achieved at 13% RH, 6 and at 10% RH on hematite. 24 The initial g of H 2 O on mineral dust (4.2 AE 0.7 Â 10 À2 ) 42 is much larger than that of NO 2 , as discussed above.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Destruction of OCS can also occur in the solid phase and was observed on pure mineral oxides with high basicity (Liu et al, 2008(Liu et al, , 2009(Liu et al, , 2010a. However, such catalytic reaction should be significant only in very dry soils (with only a few molecular layers of water) and in the absence of other competitive adsorbents such as CO 2 (Liu et al, 2008(Liu et al, , 2010b and is therefore neglected in our model.…”
Section: Consumption and Production Ratesmentioning
confidence: 99%
“…Liu and colleagues have estimated OCS adsorption capacities of several mineral oxides and found that quartz (SiO 2 ) and anatase (TiO 2 ) did not adsorb OCS but other oxides with higher basicity adsorbed, reversibly or not, rather large quantities of OCS (Liu et al, 2008(Liu et al, , 2009(Liu et al, , 2010a. They also recognised that these estimates of the adsorption capacity of the minerals were an upper limit owing to the competitive adsorption of other gases such as CO 2 , H 2 O and Burnell et al (1988) This study Sun et al (2015) (d) NO x that occur in the real Earth's atmosphere (Liu et al, 2009(Liu et al, , 2010a and the somewhat lower OCS partial pressure in ambient air compared to that used in their experimental setup. Also, at steady state, adsorption should have little influence on the soil-air OCS exchange rate, unless heterogeneous (surface) reactions occur and continuously remove OCS from the adsorbed phase (Liu et al, 2010a).…”
Section: Partitioning Of Ocs In the Different Soil Phasesmentioning
confidence: 99%
“…Interactions of water vapor with aerosol particles largely affect the roles that aerosol particles play in the Earth system. When water vapor is supersaturated (i.e., when relative humidity, RH, is > 100 %), aerosol particles can act as cloud condensation nuclei (CCN) to form cloud droplets and as ice-nucleating particles (INPs) to form ice crystals (Pruppacher and Klett, 1997;Lohmann and Feichter, 2005;Vali et al, 2015;Lohmann et al, 2016;Tang et al, 2016aTang et al, , 2018Knopf et al, 2018). Cloud condensation nucleation and ice nucleation activities of aerosol particles, as well as relevant experimental techniques, have been recently reviewed in several books and review papers (Pruppacher and Klett, 1997;Hoose and Moehler, 2012;Murray et al, 2012;Kreidenweis and Asa-Awuku, 2014;Farmer et al, 2015;Lohmann et al, 2016;Tang et al, 2016a;Kanji et al, 2017) and are thus not further discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%